2020
DOI: 10.1002/pol.20190108
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide‐mediated radical polymerization of methacryloisobutyl POSS and its block copolymers with poly(n‐acryloylmorpholine)

Abstract: Nitroxide-mediated radical polymerization (NMP) of the bulky methacryloisobutyl-polyhedral oligomeric silsesquioxane (POSS-MA) is successfully achieved after optimizing reaction conditions such as selection of controlling comonomer, comonomer feed molar ratio, and temperature (10 mol % styrene (S) comonomer at 110 C using the commercially available BlocBuilder as the NMP initiator). The P(POSS-MA-co-S) with a molecular weight of~8000 g/ mol and dispersity Ð-1.2 is afforded under the optimized reaction conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Polyethylene, polyacrylonitrile, polystyrene, poly( n ‐alkyl methacrylates) and azobenzene‐containing poly(meth)acrylates used typically as hard blocks while poly(ethylene glycol), poly(tetramethylene glycol), poly(dimethylsiloxane), polyisoprene, polybutadiene, poly(methyl acrylate), and poly(methyl methacrylate) utilized as soft blocks 38,40,66,70,77 . Generally, BCs based on hard and soft blocks are prepared by the three most commonly used methods including nitroxide‐mediated polymerization (NMP), 78,79 atom transfer racial polymerization (ATRP) 80,81 and reversible addition‐fragmentation chain transfer (RAFT) 82,83 to control their molecular weight, dispersity ( M w /M n = Đ), composition and chain architecture. The RAFT technique has recently become an almost universal synthetic strategy for producing BCs having predetermined molecular weight and very narrow dispersity because of its compatibility with various reaction conditions, its good tolerance to a wide range of functional groups and its broad applicability to most vinyl monomers when compared with the NMP and ATRP 79,84–86 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene, polyacrylonitrile, polystyrene, poly( n ‐alkyl methacrylates) and azobenzene‐containing poly(meth)acrylates used typically as hard blocks while poly(ethylene glycol), poly(tetramethylene glycol), poly(dimethylsiloxane), polyisoprene, polybutadiene, poly(methyl acrylate), and poly(methyl methacrylate) utilized as soft blocks 38,40,66,70,77 . Generally, BCs based on hard and soft blocks are prepared by the three most commonly used methods including nitroxide‐mediated polymerization (NMP), 78,79 atom transfer racial polymerization (ATRP) 80,81 and reversible addition‐fragmentation chain transfer (RAFT) 82,83 to control their molecular weight, dispersity ( M w /M n = Đ), composition and chain architecture. The RAFT technique has recently become an almost universal synthetic strategy for producing BCs having predetermined molecular weight and very narrow dispersity because of its compatibility with various reaction conditions, its good tolerance to a wide range of functional groups and its broad applicability to most vinyl monomers when compared with the NMP and ATRP 79,84–86 …”
Section: Introductionmentioning
confidence: 99%
“…The RAFT technique has recently become an almost universal synthetic strategy for producing BCs having predetermined molecular weight and very narrow dispersity because of its compatibility with various reaction conditions, its good tolerance to a wide range of functional groups and its broad applicability to most vinyl monomers when compared with the NMP and ATRP. 79,[84][85][86] Herein, this article describes the molecular design, synthesis and study of the structural and thermal properties as well as the self-assembly behavior of two series of linear hybrid AB-type hard-hard diblock copolymers (DBCs) and ABC-type hard-soft-hard triblock copolymers (TBCs) with well-defined molecular weights, dispersities, architectures, and compositions. Both BC series were obtained by typical RAFT polymerization using azobisisobutyronitrile (AIBN) as a radical initiator and anisole as a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Methacrylic POSS contain one or more methacrylic ligands, which enables free radical polymerization. Many studies have illustrated the successful radical polymerization (conventional, [ 17,18 ] atom transfer radical polymerization [ATRP], [ 19–21 ] reversible addition‐fragmentation chain transfer [RAFT] [ 22,23 ] and nitroxide mediated polymerization [NMP] [ 24,25 ] ) of methacrylic POSS. One of the methacrylic POSS compounds is 3‐(3,5,7,9,11,13,15‐heptaisobutylpentacyclo [9.5.1.…”
Section: Introductionmentioning
confidence: 99%
“…POSSMA‐rich copolymers with 10 mol% acrylonitrile (AN) or styrene (S) in the initial monomer mixture was previously synthesized in our research group using N‐(2‐methylpropyl)‐N‐(1‐(diethylphosphono‐2,2‐dimethylpropyl)‐O‐(2‐carboxylprop‐2yl)hydroxylamine) BlocBuilder‐MA (BB, Arkema). [ 24,25 ] Charleux et al [ 28 ] showed that the polymerization of methacrylate‐rich compositions (essentially mimicking homopolymerization) by BB alkoxyamine was feasible using a low concentration of controlling comonomer with a very low activation/deactivation equilibrium constant such as AN or S, which was thought to decrease the average equilibrium constant for activation/deactivation of the chains 〈 K 〉 and to also reduce cross‐disproportionation side reactions. [ 29–31 ]…”
Section: Introductionmentioning
confidence: 99%
“…4,6,8 Methacryloisobutyl POSS (termed herein as POSSMA) is a POSS containing molecules (n = 8) with one methacrylic ligand, which can be incorporated into polymer resins to improve the hardness (T g of poly(POSSMA) ≈ 85 C) 9 and thermal stability. The reversible-deactivation radical polymerization (RDRP) of POSSMA with different monomers was previously studied in organic solvents [10][11][12][13][14][15][16][17] and reported in dispersed aqueous media recently. 18 Nitroxide mediated polymerization (NMP), as one of the simplest RDRP techniques, can be used to prepare POSSMA-containing polymers with active chain ends, well-defined microstructures and narrow molecular weight distributions.…”
Section: Introductionmentioning
confidence: 99%